Temporal aspects of info-serendipity - Yosef Solomon (Temporalités)
Time has been explored under many different angles and contexts in the natural and exact sciences, as well as in the social sciences and the humanities. Nevertheless, the study of time and temporal aspects in relation to information serendipity is still in its early stages and quite limited. This article presents the topic of serendipitous information acquisition – i.e., fortuitous and unexpected discovery of valuable information – and highlights its key temporal expressions through a hermeneutic review of the current literature in the field of information science. The article explores and provides novel insights into four fundamental temporal aspects of serendipity: (1) temporal continuity and bi-directionality in the process of serendipity in information; (2) time frames of background concerns that lie at the basis of chance information encounters; (3) the semi-temporal classification of individuals who experience serendipity in information; as well as (4) temporal aspects of the benefits arising from such serendipitous episodes. The author calls for further exploration of temporal aspects involved and consecutive to such opportunistic discoveries of valuable information, within both information and time disciplines.